TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN SISTEM INFORMASI ADUAN (SIADU) DI UPN “VETERAN” JAWA TIMUR - Syafiqotul M, Nur; Kartiko, Ica Veronika; Juliana, Jamiatun; Nur W, Khovifah; Millensyah, Erwing Wahyu (The Indonesian Journal of Public Administration (IJPA), 2025)
The level of student satisfaction was measured to assess the effectiveness of the Sistem Informasi Aduan (SIADU) services at UPN "Veteran" Jawa Timur. This study employed a quantitative approach using the End User Computing Satisfaction (EUCS) model by Doll for variable X, which includes five main indicators: content, accuracy, format, timeliness, and ease of use. Meanwhile, the satisfaction of information system services as variable Y was analyzed using indicators of reliability, responsiveness, consistency, accessibility, flexibility, and trust as key indicators of user satisfaction. A sample of 393 students was obtained through simple random sampling techniques. The results of validity and reliability tests indicated that all instruments were valid. Spearman correlation analysis showed a very strong and significant relationship between the two variables (r = 0.817; sig = 0.000). Students expressed moderate satisfaction with SIADU services, with the highest scores in the content and trust indicators, and the lowest scores in timeliness and consistency. These findings emphasize the importance of improving the quality of the system and services comprehensively to enhance user satisfaction sustainably.